Permainan dalam Pembelajaran Keterampilan Berbicara di Kelas Rendah Sekolah Dasar: Sebuah Alternatif Model Pembelajaran Bahasa Bernuansa Psikolinguistik - Mohd. Hafrison (Fakultas Bahasa dan Seni UNP, 2008)
This paper is discusses the use of game in relation to some theories in the psycholinguistic area, kinds of game, and its procedures for elementary students. Game can be said as one of alternatives for joyful learning. In Psycholinguistic, it is believed that the use of game can stimulate the use of games stimulate the students’ cognitive and language development. This simulation occurs in the cognitive development and ability to use language productively, especially the ability to speak. The cognitive development and the ability to use language are one of the best techniques gained by applying these six games such as “please guess, riddles, twenty questions, charades, and let’ tell a story”. To achieve the expected result, these games need to be conducted by the appropriate procedures, of course, by analyzing students’ characteristics. It is expected that by applying these six games, the students’ difficulties in speaking can be reduced. Keywords: game, cognitive development, speaking ability, elementary students, psycholinguistics